Comparative Evaluation of the Antioxidant Properties of Whole Peanut Flour, Defatted Peanut Protein Meal, and Peanut Protein Concentrate - Asen, Nancy D.; Badamasi, Abdulhafiz T.; Gborigo, James T.; Aluko, Rotimi E.; Girgih, Abraham T. (Frontiers in Sustainable Food Systems, 2021)
Defatted peanut meal is a low value agro-industrial residue from peanut oil production with potential use as a value addition food ingredient. In this study, peanuts were roasted at 100°C for 5 min, de-skinned and milled into whole peanut flour (WPF) from which the defatted meal (DPM) was prepared by acetone extraction and the peanut protein concentrate (PPC) obtained from the DPM using isoelectric pH precipitation. The protein content, amino acid profile, total phenolic content (TPC), total flavonoid content (TFC) and in vitro antioxidant properties of the peanut samples were then determined. Results showed that DPM had a TPC of 0.12 ± 0.02 mg gallic acid equivalent (GAE)/g, which was significantly (p < 0.05) higher than and twice the levels in WPF and PPC (0.06 ± 0.03 mg GAE/g). However, WPF had TFC of 0.21 ± 0.01 μg quercetin equivalent (QE)/g, which was significantly (p < 0.05) higher than DPM (0.16 ± 0.03 μg QE/g) and PPC (0.11 ± 0.05 μg QE/g). However, PPC had superior amino acid profile in addition to stronger radical scavenging and metal chelation activities than WPF and DPM. The results suggest that PPC is a protein rich product that could be utilized as an ingredient in food product fortification to enhance nutritional quality and in the formulation of functional foods with antioxidant benefits.